Effect of adding magnifying BLI, magnifying NBI, and iodine staining to white light imaging in diagnosis of early esophageal cancer - Kawada, Kenro; Arima, Miwako; Miyahara, Ryoji; Tsunomiya, Mika; Kikuchi, Masakazu; Yamamoto, Fumiko; Hoshino, Akihiro; Nakajima, Yasuaki; Kinugasa, Yusuke; Kawano, Tatsuyuki (Endoscopy International Open, 2021)
Background and study aims We investigated the effect of adding magnifying blue laser imaging (BLI), magnifying narrow-band imaging (NBI), and iodine staining to white light imaging in diagnosis of early esophageal squamous cell carcinoma (EESCC) in high-risk patients.Patients and methods Between May 2013 and March 2016, two parallel prospective cohorts of patients received either primary WLI followed by NBI-magnifying endoscopy (ME) or primary WLI followed by BLI-ME, were studied. At the end of screening, both groups underwent iodine staining. The percentage of patients with newly detected esophageal malignant lesions in each group and the diagnostic ability of image-enhanced endoscopy (IEE)-ME were evaluated.Results There are 258 patients assigned to the NBI-ME group and 254 patients assigned to the BLI-ME group. The percentage of patients with one or more malignant lesions detected in the WLI + NBI-ME examination was similar in the WLI + BLI-ME examination (15 of 258 patients or 5.81 % vs. 14 of 254 patients or 5.51 %). However, four of 19 lesions in the NBI-ME group and six of 21 lesions in the BLI-ME group were overlooked and were detected by iodine staining. NBI-ME and BLI-ME showed similar accuracy in differentiation of cancerous lesions from non-cancerous lesions in diagnosis of EESCC (NBI/BLI: sensitivity, 87.5/89.5; specificity, 78.9/76.6; accuracy, 80.8/79.5; positive predictive value, 53.8/53.1; negative predictive value, 95.7/96.1).Conclusions Both NBI and BLI were useful for detection of EESCC. However, because some lesions were overlooked by even NBI and BLI, high-risk patients may benefit from use of iodine staining during endoscopic screening of EESCC (UMIN000023596).